2023
DOI: 10.1186/s43093-023-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of macroeconomic and institutional environment on NPL of developing and developed countries

Shikha Goyal,
Nikita Singhal,
Nandita Mishra
et al.

Abstract: The study investigates what causes non-performing loans (NPLs) in developed and developing countries. To identify the relationship between bank-specific, macroeconomic determinants, and institutional environment non-performing loans on country-level panel data of Developing nations for the period extending from 2010 to 2020, the author used panel system GMM methodology. The long-held hypothesis that NPLs contribute to economic growth is tested using the Panel Granger causality test. Further panel cointegration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…The results were carried out by Tanjung et al (2022), where inflation significantly affects bank credit. Table 5 shows The results of the variable causality test with the Granger causality test; it was found that, in general, the causal relationship formed in this study was that the variables used were unidirectional (Goyal et al, 2023). That is, changes between one variable and another are responded to without any reciprocal relationship.…”
Section: Vecm Test Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…The results were carried out by Tanjung et al (2022), where inflation significantly affects bank credit. Table 5 shows The results of the variable causality test with the Granger causality test; it was found that, in general, the causal relationship formed in this study was that the variables used were unidirectional (Goyal et al, 2023). That is, changes between one variable and another are responded to without any reciprocal relationship.…”
Section: Vecm Test Analysismentioning
confidence: 76%
“…Inflation has a one-way relationship with ROA, but ROA does not. Inflation is believed to be a macroeconomic variable that can affect the profitability of Islamic banks but cannot be strongly influenced by bank performance (Goyal et al, 2023).…”
Section: Granger Causality Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Capital Adequacy Ratio (CAR) digunakan untuk melihat determinan NPL berdasarkaan faktor bank specific, seperti pada penelitian Makri et al (2014), Radivojevic & Jovovic (2017), Raiter (2021), Kryzanowski et al (2023), Goyal et al (2023). Penelitian ini menggunakan data CAR triwulanan.…”
Section: Capital Adequacy Ratio (Car)unclassified
“…Hasil pengujian statistik menunjukkan bahwa Capital Adequacy Ratio (CAR) tidak berpengaruh terhadap NPL. Hasil ini sejalan dengan penelitian Raiter (2021) dan Goyal et al (2023). Hasil ini menunjukkan bahwa perbankan di negara Kawasan ASEAN memiliki cadangan modal yang mencukupi untuk melindungi diri dari risiko kredit dan risiko-risiko lainnya.…”
Section: Pengaruh Suku Bunga Bank Sentral Terhadap Non-performing Loa...unclassified